Real-world outcomes and factors impacting treatment choice in relapsed and/or refractory multiple myeloma (RRMM): a comparison of VRd, KRd, and IRd - Chari, Ajai; Richardson, Paul G; Romanus, Dorothy; Dimopoulos, Meletios A; Sonneveld, Pieter; Terpos, Evangelos; Hajek, Roman; Raju, Aditya; Palumbo, Antonio; Cain, Lauren E; Blazer, Marlo; Huang, Hui; et al. (Expert review of hematology, 2020)
Lack of head-to-head trials highlights a need for comparative real-world evidence of proteasome inhibitors plus Rd.Methods: In this retrospective, US population-representative EHR study of RRMM patients initiating IRd, KRd, or VRd in line of therapy (LOT) ≥2 between 1/2014 and 9/30/2018, 664 patients were treated in LOT ≥2 with: IRd, n = 168; KRd, n = 208; VRd, n = 357. Median age was 71/65/71 years; 67%/70%/75% had a frailtymodified score of intermediate/frail; 20%/28%/13% had high cytogenetic risk in I-/K-/V-Rd groups. Risk of PI-triplet discontinuation was lower for I- vs. K-Rd (HR: 0.71) and I- vs. V-Rd (HR: 0.85); unadjusted, median TTNTs (months): 12.7/8.6/14.2 (LOT ≥2) and 16.8/9.5/14.6 (LOT 2-3) (I-/K-/V-Rd). Adjusted TTNT was comparable between I-/K-/V-Rd in LOT ≥2 with a TTNT benefit among intermediate/frail patients for I- (HR: 0.70; P=0.04) and V- (HR: 0.73; P<0.05) vs. K-Rd. I/K/V-Rd triplets were comparable in TTNT overall, but IRd and VRd were associated with longer TTNT in intermediate/frail patients than KRd. The results suggest a trial-efficacy/real-world-effectiveness gap, especially for KRd, underlining the limited generalizability of trial results where >50% of patients are excluded. Individualized treatment based on patient characteristics, such as frailty status, is especially pertinent in an elderly RRMM population.
Keywords: Disease-Free Survival; real world; Male; retrospektivní studie; Risk Factors; Survival Rate; Antineoplastic Combined Chemotherapy Protocols; PI-triplet therapy; Aged; Multiple Myeloma; mužské pohlaví; senioři; Bortezomib; RRMM; proteasome-inhibitor-triplet therapy; lidé; ženské pohlaví; relapsed refractory multiple myeloma; Humans; protokoly protinádorové kombinované chemoterapie; rizikové faktory; carfilzomib; Retrospective Studies; mnohočetný myelom; Female; lidé středního věku; přežití bez známek nemoci; míra přežití; ixazomib; Middle Aged